Nanopore Structure and Mechanical Properties in Brittle Tectonically Deformed Coals Explored by Atomic Force Microscopy - Zhang, Ningyuan; Yao, Suping; Wang, Yuhui (Frontiers in Earth Science, 2022)
Tectonically deformed coals (TDCs) are of great importance to coalbed methane exploitation and coal mining safety. Compared to primary coals, reservoir properties of TDCs have been transformed greatly by tectonic stress. Here, the pore structure and mechanical properties of brittle TDCs were obtained with atomic force microscopy (AFM) and software. The results showed that tectonic stress generally promotes pore development and Young’s modulus of brittle TDCs. According to the variation in pore structure and Young’s modulus, two stages were identified: weak brittle deformation stage (primary coal–cataclastic coal–schistose coal–mortar coal) and strong brittle deformation stage (mortar coal–granulitic coal–flaky coal). The extent of tectonic impact varies greatly between these two stages. In weak brittle deformation stage, tectonic stress has little impact on coal pore structure. The mean pore number increases slowly, and the mean pore size decreases slowly. In this stage, half of the pore number increment is provided by macropores of 100–200 nm diameter. In strong brittle deformation stage, tectonic stress has a major impact on coal pore structure. The mean pore number increases quickly, and the mean pore size decreases quickly. Most of the pore number increment comes from mesopores of 10–50 nm diameter and macropores of 50–100 nm diameter. In addition, the Young’s modulus of different brittle TDCs varies from 1.5 GPa to 2.0 GPa. In weak brittle deformation stage, the Young’s modulus of different samples levels off. While in strong brittle deformation stage, the Young’s modulus increases gradually. Combined with former studies, it is inferred that tectonic stress can influence coal’s Young’s modulus by transforming its chemical structure.